Motor control exercises versus general exercises for greater trochanteric pain syndrome: A protocol of a randomized controlled trial - Thomaz de Aquino Nava, Guilherme [UNESP]; Baldini Prudencio, Caroline [UNESP]; Krasic Alaiti, Rafael; Mendes Tozim, Beatriz [UNESP]; Mellor, Rebecca; Rodrigues Pedroni, Cristiane [UNESP]; Mércia Pascon Barbosa, Angélica [UNESP]; Tavella Navega, Marcelo [UNESP] (Public Library of Science (PLoS), 2022)
INTRODUCTION: Greater trochanteric pain syndrome is an overarching term used to define pain and tenderness in the greater trochanteric region of the femur, which is more common in women. Abnormal control of lower limb movements and deficient neuromuscular parameters may lead to greater trochanteric pain syndrome; however, no studies have used neuromuscular training as a treatment strategy. Thus, this study aims to compare the effect of a protocol of general exercises versus a program of motor control training on pain at baseline and after treatment in women with greater trochanteric pain syndrome. METHODS: The study was approved by the Research Ethics Committee (CAAE: 87372318.1.0000.5406) and has been prospectively registered on the Brazilian Registry of Clinical Trials (RBR-37gw2x). Sixty participants will be randomized to receive motor control exercises or general exercises. The application will be performed twice a week for 8 weeks. The participants will be evaluated before the treatment (T0), after 8 weeks of intervention (T8) and after 60 weeks of intervention (T60). The primary outcome measures will be the hip pain intensity, and secondary outcomes will be muscle strength, kinesiophobia, global perceived effect, pain catastrophization, central sensitization and quality of life. CONCLUSIONS: Studies have suggested that greater trochanteric pain syndrome may be related to poor hip and pelvic control, however, no study has investigated an exercise protocol focused on increasing the strength of the abductor and extensor muscles of the hip associated with pelvic control training, especially in positions of unilateral support, such as gait. This study will help determine whether greater trochanteric pain syndrome is related to abnormal control of lower limb movements.